Estimating the Students’ Skill in Reciting and Writing Alqur’an at Faculty of Tarbiyah and Teacher Training IAIN Sultan Amai Gorontalo - Otaya, Lian G.; Anwar, Herson; Husain, Rahmin Talib (FITK UIN Walisongo, 2019)
The purpose of this study was to estimate the instrument of reading and writing capability of the Qur’an in the practicum program students of the Faculty of Tarbiyah and Teacher Training IAIN Sultan Amai Gorontalo. This type of research is quantitative with an analysis approach to the generalization theory variance through the G-Study concept with a multifacet design p x r x I three facet variations. The results of the study prove the instrument of reading and reading ability of the Koran was tested, namely the estimated coefficient of reliability of the combined scores of the reading and writing assessment of the Koran from 20 students who were rated by 4 rater of 10 items which were judged by the magnitude of generalizability coefficient value of 0.82749 . The magnitude of this value indicates that the true score of the assessment results is quite high compared to the minimum reliability criteria, which is 0.70 fulfilling the reliable criteria. AbstrakTujuan penelitian ini untuk mengestimasi instrument kemampuan baca tulis alqur’an pada program praktikum baca tulis Alqur’an mahasiswa Fakultas Ilmu Tarbiyah dan Keguruan IAIN Sultan Amai Gorontalo. Jenis penelitian ini menggunakan kuantitatif dengan pendekatan analisis varians teori generalisibilitas melalui konsep G-Study dengan desain multifacet p x r x I tiga variasi facet. Hasil penelitian membuktikan instrumen penilaian kemampuan baca tulis al-Qur’an teruji, yakni estimasi koefisien reliabilitas skor gabungan penilaian kemampuan baca tulis Alqur’an dari 20 mahasiswa yang dinilai oleh 4 rater terhadap 10 item yang dinilai diperoleh besarnya nilai koefisien generalizabilitas sebesar 0,82749. Besaran nilai tersebut menunjukkan bahwa true score hasil penilaian cukup tinggi dibandingkan kriteria reliabilitas minimal yaitu 0,70 memenuhi kriteria reliabel.